ORGANIZATIONAL JUSTICE, WORK-LIFE BALANCE, AND TURNOVER INTENTION: MEDIATING ROLE OF EMPLOYEE ENGAGEMENT IN XYZ HOTEL EMPLOYEES - Chan, Jefry; Turangan, Joyce Angelique (Graduate Program of Universitas Tarumanagara, 2024)
The trend of turnover intention in the hotel industry poses a significant challenge, particularly with the high intentions of Generation Z and millennials to leave their jobs, as revealed in the surveys conducted by Achievers Workforce Institute 2023 and Indonesia Millennial Report 2019. Data from Michael Page International Indonesia 2022 highlights a significant wave of resignations, especially in the leisure, travel & tourism sectors. XYZ Hotel with a workforce of a hundred employees, is experiencing the impact of job turnover trends. This study aims to examine the influence of organizational justice and work-life balance on turnover intention, with employee engagement as a mediating factor, among employees at Hotel XYZ. The population of this study includes all employees working at XYZ Hotel. A total of 100 samples were obtained using the total sampling method. The collected data were processed using SmartPLS 3. The results of this study indicate that the variables of organizational justice and employee engagement have a negative and significant influence on turnover intention. Meanwhile, work-life balance has a positive and significant influence on turnover intention in XYZ Hotel and must be mediated by employee engagement to achieve a negative effect.